Pengenalan Teknologi Digital dan Etika Online melalui POSASI (Poster Edukasi) sebagai Upaya Pencegahan Cyberbullying di Kalangan Siswa MTs Al-Ittihad - Sholikhah, Muthiatus; A, Fathur Rohman Devin; Nugraha, Rifki Artha; Untari, Sri (Al-DYAS, 2025)
MTs Al Ittihad, located in Malang Regency, East Java, faces serious challenges related to bullying, both physical and through social media (cyberbullying). Malang Regency has reported 65 cases of bullying, an increase from 42 cases in 2021. The causes of bullying can be categorized into two groups: internal and external factors. Internal factors include the inability to manage emotions, where individuals with trauma, such as victims of broken homes, tend to express anger and frustration through bullying behavior. External factors encompass environment, peer relationships, and family; for instance, if someone grows up in an environment that promotes violence, they are more likely to engage in bullying. With the advancement of technology, bullying now occurs not only physically but also on digital platforms, known as cyberbullying. Actions like negative comments on social media can disrupt the mental well-being of victims and diminish their concentration in learning. To address this issue, a community service team is implementing the program “Introduction to Digital Technology and Online Ethics Through POSASI (Educational Posters).” This program aims to create a safe and inclusive school environment, reminding students of the importance of respecting differences, protecting one another from cyberbullying, and fostering a positive culture among MTs Al Ittihad students.